2011
DOI: 10.1111/j.1755-3768.2010.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

The vitreomacular interface in retinal vein occlusion

Abstract: ABSTRACT.Purpose: To evaluate the posterior vitreous adhesion status in patients with a history of central or branch retinal vein occlusion and to compare the results with the natural time-course of posterior vitreous detachment in healthy agerelated controls. Methods: A retrospective chart review in terms of the posterior vitreous adhesion status was performed in 132 patients (133 eyes) with a history of a central (CRVO) or branch (BRVO) retinal vein occlusion. All patients underwent vitrectomy. Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
0
20
1
1
Order By: Relevance
“…Bertelmann et al showed that the posterior vitreous cortex in patients with a history of BRVO attached more frequently to the retina, compared with healthy age-matched controls [18]. We did not detect apparent vitreomacular traction by ophthalmoscopy and OCT at the first visit in this series of patients.…”
Section: Discussioncontrasting
confidence: 54%
“…Bertelmann et al showed that the posterior vitreous cortex in patients with a history of BRVO attached more frequently to the retina, compared with healthy age-matched controls [18]. We did not detect apparent vitreomacular traction by ophthalmoscopy and OCT at the first visit in this series of patients.…”
Section: Discussioncontrasting
confidence: 54%
“…They found that 58.5% of patients with a vein occlusion developed CPVD by 6 months, with 69.6% having a PVD by 12 months as compared to 25% in the control group at both 6 and 12 months of follow-up. Records of patients undergoing an optic neurotomy or arteriovenous sheath separation indicated that the vast majority of patients had an intact posterior vitreous face prior to surgery (central retinal vein occlusion 56/61 patients; branch retinal vein occlusion 35/38) [127], an incidence which according to the authors is much higher than expected from historical controls obtained by ultrasonography. Imaging using spectral-domain OCT revealed a high frequency of perifoveal traction but was less frequently identified than with surgery [128].…”
Section: Influence Of Pvd In Selected Retinal Pathologies - Meta-analmentioning
confidence: 92%
“…An attached or partially detached PVC leads to the development and expeditious progression of BRVO [2,5,6,24]. Visual impairment is, besides other mechanisms, often attributed to a consecutive macular edema [16] or neovascularization development [2] and the adhesion status was postulated as one risk factor for the development of both complications [24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreally applied anti-vascular endothelial growth factor (VEGF) as well as corticosteroids have recently improved the further course of the disease dramatically [3,4]. Nevertheless, posterior vitreous cortex (PVC) adhesion was demonstrated to support the development of retinal vein occlusion [5,6]. It has furthermore an impact on CME chronicity and the rate of neovascularization development within the eye [2].…”
Section: Introductionmentioning
confidence: 99%